Synthesis And Pharmacological Evaluation of Some Novel Benzhydryl Piperazine Derivatives for Anti-Cancer Activity - Kumar, Aadesh; Bharati, Dileep Kumar; Khadanga, Manasi; Chakraborth, Gunosindhu; Rout, Bhabani Shankar; Mohapatra, Swosti; Parida, Janmejay; Parija, Swalin (Journal of Neonatal Surgery, 2025)
The creation of novel anticancer drugs is required to address the issues of toxicity and adverse effects. Derivatives of benzohydryl piperazine have recently been discovered to have cytotoxic and nanomolar epidermal growth factor receptor (EGFR) inhibitory action. The impact of benzhydryl piperazine derivatives on anticancer activity has been investigated in this work. Using gefitinib as the reference, a panel of three cancer cell lines—human pancreatic carcinoma (MIAPaCa-2), human colon carcinoma (HCT-116), and adenocarcinomic human alveolar basal epithelial cells (A-549)—were used to assess a series of six benzhydryl piperazine derivatives. According to the data, the majority of the compounds had encouraging efficacy; however, compound 3c was the most active, exhibiting cytotoxicity significantly superior to that of gefitinib. 4.63 µM against the HCT-116 colon cancer line, 30.11 µM against the MIAPaCa-2 cell line, and 5.71 µM against the A-549 cell line were its IC50 values. These substances will be discovered to be well suited to the active site and might be demonstrating anticancer potential through EGFR inhibition